AGRARIAN REFORM: LEGAL CHALLENGES IN TRANSMIGRATION LAND LEGALIZATION - Mujiburohman, DianAries; Salim, M Nazir; Junarto, Rohmat (Fakultas Hukum, Universitas Islam Balitar, 2025)
This research examines various challenges related to the legalization and redistribution of transmigration land, using a normative juridical approach and secondary data. The research results show that the transmigration program, although based on strong laws and continuously being updated, only succeeded in achieving 23.14% of the set land area target, namely 138,834.72 hectares from the target of 0.6 million hectares. Several problems hinder this process, such as transfers and sales, illegal transfers, disputes with the business world, disputes between government agencies, overlapping claims on forest areas, and a lack of accurate legal and spatial data. This complexity causes legal uncertainty regarding transmigration land, thereby creating obstacles to land ownership. To overcome this problem, a multi-faceted strategy is needed that includes establishing a clearer legal framework, investing in infrastructure to speed up land registration, strengthening cooperation between institutions, increasing transparency in land administration, and increasing public awareness through education and empowerment. These strategic steps are important to ensure legal certainty, protect the rights of transmigrants, and support broader goals, namely fair land distribution and regional development.